Slight synthetic changes eliciting different topologies: synthesis, structure and magnetic properties of novel dinuclear and nonanuclear dysprosium complexes. Issue 46 (29th October 2015) - Kuo, Che-Jung; Holmberg, Rebecca J.; Lin, Po-Heng
Abstract : Using the Schiff-base ligand, H2 hmc, dinuclear and nonanuclear compounds are generated through the addition of different bases. The unique Dy9 core structure of complex2 was obtained and the magnetic properties of both compounds are fully studied. Abstract : Using the Schiff-base ligand 1, 5-bis(2-hydroxy-3-methoxybenzylidene)carbonohydrazide (H2 hmc), dinuclear and nonanuclear compounds, [Dy2 (Hhmc)2 (NO3 )4 ]·THF·MeCN (1 ) and [Dy9 (μ3 -O)4 (μ-OH)6 (hmc)4 (NO3 )4 (DMF)4 ](OH)·H2 O·THF·DMF (2 ) are generated through the addition of different bases, respectively. Single-crystal X-ray diffraction analysis revealed a unique Dy9 core structure of complex2, and the magnetic properties of both compounds are fully studied.